2013
DOI: 10.1093/ndt/gft462
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-lowering drugs in patients with chronic kidney disease: a narrative review on pharmacokinetic properties

Abstract: The achievement of a good glycaemic control is one of the cornerstones for preventing and delaying progression of microvascular and macrovascular complications in patients with both diabetes and chronic kidney disease (CKD). As for other drugs, the presence of an impaired renal function may significantly affect pharmacokinetics of the majority of glucose-lowering agents, thus exposing diabetic CKD patients to a higher risk of side effects, mainly hypoglycaemic episodes. As a consequence, a reduction in dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 92 publications
0
83
0
5
Order By: Relevance
“…In general, first-generation sulfonylureas should be avoided in patients with CKD stages 3 or 4 or those who are undergoing dialysis, in whom gliclazide and glipizide are suitable without extensive dose adjustment [71][72][73] . Glimepiride is an option for patients with CKD but not receiving dialysis, on the proviso of low-dose initiation and careful titration 71,73 .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In general, first-generation sulfonylureas should be avoided in patients with CKD stages 3 or 4 or those who are undergoing dialysis, in whom gliclazide and glipizide are suitable without extensive dose adjustment [71][72][73] . Glimepiride is an option for patients with CKD but not receiving dialysis, on the proviso of low-dose initiation and careful titration 71,73 .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Similarly, the SAVOR-TIMI 53 trail, 12 which uses a prespecified renal safety composite endpoint, showed that saxagliptin did not increase the risk of impaired kidney function. However, in spite of this, dose adjustment is recommended for all medications except linagliptin 13 (because 80% of linagliptin is eliminated unchanged in feces 14 ). In general, DPP-4 inhibitors are fairly tolerable and safe.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a leading cause of kidney damage and develops chronic kidney disease later in life [8] . This is because of haemodynamic changes and further free radical generation in hyperglycaemia [9,10] .…”
Section: Research Papermentioning
confidence: 99%
“…But, the metabolism is incomplete due to lack of tolerance of the organs to different drug doses. Conversely, nonmetabolized content of the hypoglycaemic agent, which accumulates in the above organs worsened their normal functions [8] .…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation